Power Quality Improvement Using Multi-level Inverter based DVR and DSTATCOM Using Neuro-fuzzy Controller - G. Ramya; V. Ganapathy; P. Suresh (Institute of Advanced Engineering and Science, 2017)
STATCOM is one of the shunt type FACTS controllers which can supply reactive power and improve bus voltage. STATCOM, a controlling device used on alternating current transmission networks, has advantages like transient free switching and smooth variation of reactive power. This paper proposes a cascaded multilevel inverter type DSTATCOM and DVR to compensate voltage sag in utilities in power distribution network. The proposed DSTATCOM is implemented using multilevel topology with isolated dc energy storage and reduced number of switches. A DVR injects a voltage in series with the system voltage and a D-STATCOM implant a current into the system to correct the voltage sag, swell and interruption. The phase shifter PWM technique is described to generate firing pulse to cascaded inverter. The proposed neuro-fuzzy controller follow itself to the sag and provides effective means of mitigation. The voltage sag with the minimum harmonic at the efficacy end. The proposed technique is simulated using MATLAB/Simulink.